Analysis Level of Digital Literacy of Digital Natives: How The Impact On Their Self-Regulated Learning? - Jannah, Syayyidah Maftuhatul (Ekspektra : Jurnal Bisnis dan Manajemen, 2019)
This study aims to analyze the level of digital literacy of millennial generation and how it affects their abilities in their learning process (self-regulated learning). Data were obtained through an online questionnaire distributed to students at several universities in Yogyakarta. The number of questionnaires that can be processed is 100 questionnaires. Furthermore, the collected data is then analyzed using Structural Equation Modeling (SEM). The results showed that the level of digital literacy of female students could be said to be higher than that of male students. However, both male and female students have not so high scores on the dimensions of critical understanding as one dimension of digital literacy. The results of this study also show that digital literacy has a positive effect on self-regulated learning.